Biosensor and Chemosensor Fluorophores that contain Chalcogenide Centers - Yudhistira, Tesla; Lee, Woo Hyun; Churchill, David G (Makara Journal of Science, 2020)
In this timely review, we discuss the important attributes of various chalcogen-containing small-molecule probes that have been synthesized in the Molecular Logic Gate Laboratory at the Korea Advanced Institute of Science and Technology. Specifically, we discuss some of the important chemical and photophysical properties of these probes, including reversibility, responsiveness (response time), cellular localization, sensitivity to analytes, selectivity (toward a specific analyte in question), and some bioavailability criteria. Chalcogenides undergo reversible redox-type reactions with reactive oxygen species (ROS). These controlled solution reactions enable a sensible and clear response as they act to immediately affect the chemical and electronic properties of the chalcogen moiety. Often, the lone pair belongs to chalcogens, which communicate electronically with the rest of the probes. Importantly, chemically oxidized chalcogenides can revert to their original reduced (divalent) form through the addition of natural or unnatural biothiols (or other reductants). This phenomenon is considered reversibility from the standpoint of probes. It can also be called “resetability.” In this manner, a variety of fluorophore frameworks can be used to detect ROS and thiols. Further studies can help experimentally determine the lipophilicity and even the cellular localization of probes, which are important in assessing their value as diagnostic agents in biological sciences and their possible therapeutic potential.